PENGEMBANGAN MEDIA DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB DI KELAS VII MTSN YOGYAKARTA I - Dini Latifah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2016)
This study aims to determine the effectiveness of diorama media and whether there is a significant difference in improving the learning outcomes of Arabic language in terms of the reading skills of class VII students of MTsN Yogakarta I. The test of the instrument using the validity and reliability test showed that 25 test questions all proved valid and reliable with a reliability coefficient of 0.957 for multiple choice and 0.978 for essay. Before the data were analyzed, the data should be tested by kolmogorov smirnov test and Varian analysis test (ANOVA) to know that the data were normally distributed and homogeneous. Furthermore, the data were tested with "t" test with paired-samples T test to know the significance of pre-test and post-test of the experiment and control classes and to know the effect or influence of diorama media in improving the learning result of Arabic especially on reading skill of class VII students of MTsN Yogyakarta I academic year 2014/2015. The calculation results show that the significance of 0.000 is less than 0.05 so it is stated as significant. The results show that learning Arabic with diorama media is more effective than book media in helping to improve learning result of Arabic language in terms of reading skill of students of class VII MTsN Yogyakarta I academic year 2014/2015 and there is a significant difference between reading by using diorama media and by reading without diorama media.